The Dynamics of Pedagogical Transformation of Teachers and Student Learning Experience in the P5 Project: A Thematic Analysis in the Era of Independent Learning - Hasmira Said; Pahenra A. Nongko; Yaman La Ndibo; Ridwan J. Deluma (Research Journal on Teacher Professional Development, 2026)
This research aims to explore in depth the pedagogical transformation of teachers and subjective experiences of students in the implementation of the Pancasila Student Profile Strengthening Project (P5) at Senior High School (SMA) Muhammadiyah Kota Kendari. Using qualitative approaches and thematic analysis, the research reveals how curriculum flexibility triggers a shift in the role of teachers from conventional teachers to more creative facilitators in designing contextual learning. The findings identified that P5 projects effectively create a "safe to fail" learning environment  , which significantly improves agency, active collaboration, as well as student learning independence. Despite facing serious structural obstacles in the form of low input dimensions of digital means and the instability of technological infrastructure in non-metropolitan areas, the school demonstrated  outstanding organizational resilience through adaptive pedagogical improvisation strategies. The integration of Islamic values, such as the ethos of Man Jadda wa Jada, has proven to be a crucial compensatory factor that strengthens the intrinsic motivation and disciplined character of students in the midst of limited physical facilities. The autonomy of teachers in designing projects that are relevant to local wisdom is the main key to the success of this educational transformation. The research concludes that synchronization between independent curriculum policies and equitable infrastructure support is very urgent to ensure the fairness of the quality of national education